2021
DOI: 10.1038/s41598-021-98644-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aβ-derived peptide fragments on fibrillogenesis of Aβ

Abstract: Amyloid β (Aβ) peptide aggregation plays a central role in Alzheimer’s disease (AD) etiology. AD drug candidates have included small molecules or peptides directed towards inhibition of Aβ fibrillogenesis. Although some Aβ-derived peptide fragments suppress Aβ fibril growth, comprehensive analysis of inhibitory potencies of peptide fragments along the whole Aβ sequence has not been reported. The aim of this work is (a) to identify the region(s) of Aβ with highest propensities for aggregation and (b) to use tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 109 publications
(131 reference statements)
2
12
1
Order By: Relevance
“…Circular dichroism (CD) experiments, performed in a time range of 96 h (Figure b), reveal that Aβ 8‑20 adopts a random coil conformation over time. Interestingly, our results differ from those obtained by Abedin et al for the Aβ 11‑20 fragment which shows, despite the high sequence homology, a high propensity to form a β-sheet-rich structure . The absence of any significant secondary structure transition, typical of amyloid fiber formation, supports well ThT results, although it is not possible to exclude the formation of amorphous aggregates.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…Circular dichroism (CD) experiments, performed in a time range of 96 h (Figure b), reveal that Aβ 8‑20 adopts a random coil conformation over time. Interestingly, our results differ from those obtained by Abedin et al for the Aβ 11‑20 fragment which shows, despite the high sequence homology, a high propensity to form a β-sheet-rich structure . The absence of any significant secondary structure transition, typical of amyloid fiber formation, supports well ThT results, although it is not possible to exclude the formation of amorphous aggregates.…”
Section: Resultscontrasting
confidence: 87%
“…Interestingly, CD spectra (Figure b, inset) reveal a mixture of the random coil and β-sheet structure at t = 0 which evolves over 24 h into a random coil/α-helix. Thus, our data suggest that Aβ 8‑20 could interfere with the aggregation process of both Aβ 1‑40 and Aβ 1‑42 already at a 1:1 molar ratio, suggesting a higher efficiency than, for example, that of Aβ 11‑20 …”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies on Aβ42 aggregation have shown that the 16 KLVFFAE 22 and C-terminal 29 GAIIGLMVGGVVIA 42 regions exhibit faster aggregation propensities. 60 Both compounds 7a and 7b contain planar aromatic bicyclic ring systems (either a benzofuran or a benzothiophene ring) along with a phenyl ring. Molecular docking studies show that the aromatic bicyclic and phenyl rings present in these two compounds can undergo π-alkyl interactions with nonpolar amino acids including Leu17, Val18, Al21, and Leu34.…”
Section: The Coupling Reagents N-(3-(dimethylamino)propyl)-n′-ethyl-mentioning
confidence: 99%